Method for preparing high-performance alkaline pellets by extracting vanadium from vanadium-titanium magnetite concentrate through acid leaching

By leaching vanadium with dilute sulfuric acid and optimizing the roasting process, the vanadium recovery and reduction degree of vanadium iloxane concentrate pellets are improved, and the problems of low vanadium recovery and serious reduction and powdering of the pellets during blast furnace smelting are solved, thus realizing the preparation of high-performance alkaline pellets.

CN119876601APending Publication Date: 2025-04-25CENT SOUTH UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411977681.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

During blast furnace smelting, vanadium iloxane concentrate pellets have problems such as low vanadium recovery rate, serious reduction powdering and relatively low reduction degree. The compressive strength of vanadium pellets after roasting is difficult to meet the blast furnace requirements.

Method used

Dilute sulfuric acid is used to leach vanadium-extract vanadium-titanium iron concentrate alkali pellets, which significantly improves the porosity of vanadium-extract residual balls, and desulfurization and consolidation of vanadium-extract residual balls through an optimized roasting and heating system to improve the compressive strength of the pellets.

Benefits of technology

The vanadium recovery and reduction degree of vanadium iloxane concentrate pellets has been significantly improved, the compressive strength and porosity of the pellets have been enhanced, and the physical and metallurgical performance requirements of the pellet ore for blast furnaces has been met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876601A_ABST
    Figure CN119876601A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of metallurgy, and particularly relates to a method for preparing high-performance alkaline pellets by extracting vanadium from vanadium-titanium magnetite concentrate through acid leaching. According to the method, vanadium-titanium-iron concentrate is used as a raw material, vanadium is leached out from alkaline pellets through dilute acid, the pellets obtained after vanadium extraction through acid leaching are soaked in a ferrous sulfate solution, residual pellets obtained after solid-liquid separation are directly roasted, and roasted pellets are obtained; the obtained roasted pellets comprise the following components in percentage by mass: 52 to 62 percent of TFe, 9 to 20 percent of TiO2, 0.05 to 0.2 percent of V2O5 and less than 0.005 percent of sulfur; the porosity of the roasted pellets is 24-30%, and the compressive strength is greater than 2500N / pellet. The designed process is simple, and the pellet performance is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metallurgy, and in particular relates to a method for preparing high-performance alkaline pellets by acid leaching vanadium from vanadium-titanium magnetite concentrate. Background Art

[0002] Vanadium-titanium magnetite is an important strategic mineral resource with extremely high comprehensive utilization value. my country's vanadium-titanium magnetite reserves rank third in the world, with 10 billion tons in Panzhihua, Sichuan, and 8 billion tons in Chengde, Hebei. Vanadium-titanium magnetite is mainly composed of iron, accompanied by valuable metal elements such as titanium and vanadium. Since vanadium-titanium magnetite has the highest iron content, it is currently mainly used as a raw material for blast furnace ironmaking.

[0003] Blast furnace ironmaking mainly uses high-basicity sintered ore and acidic pellets as the main blast furnace charge to control the slag basicity. However, the sintering process of vanadium-titanium magnetite is prone to form perovskite bonding phase. Compared with calcium ferrite bonding phase, perovskite has low strength and high brittleness, resulting in low yield of vanadium-titanium iron concentrate sintered ore, poor strength, and severe reduction and pulverization, which is not conducive to the smooth blast furnace smelting. In addition, the blast furnace smelting process is a strong reducing atmosphere, and the reducing atmosphere in the smelting process is difficult to control, causing the titanium oxide in the slag to be easily over-reduced to form TiC, which in turn leads to increased slag viscosity and difficulty in separating slag from iron. Compared with the sintering production process, the pellet production process has low carbon emissions and less pollution. The development of vanadium-titanium iron concentrate pellets is an effective way to achieve low-carbon emission reduction preparation of ironmaking furnace charge. The smelting performance of alkaline pellets is better than that of acidic pellets, and the iron grade is higher than that of sintered ore. Increasing its proportion in the furnace can reduce the proportion of high-basicity sintered ore in the furnace and reduce pollutant emissions in the preparation process of ironmaking furnace charge. In addition, increasing the proportion of alkaline pellets of vanadium-titanium iron concentrate in the blast furnace smelting process can increase the oxygen potential of the blast furnace hearth, avoid over-reduction of slag and the formation of TiC, and facilitate the smooth blast furnace smelting. Therefore, the development of alkaline pellets of vanadium-titanium iron concentrate is of great significance to improving the comprehensive utilization level of vanadium-titanium magnetite.

[0004] However, when the vanadium-titanium iron concentrate pellets are reduced in the solid charge area of ​​the blast furnace, the pellets undergo significant volume expansion when the titanium hematite is reduced to the titanium magnetite stage, which leads to pulverization problems, thus affecting the permeability of the blast furnace. At the same time, vanadium-titanium iron concentrate is a typical complex iron ore. Titanium atoms partially replace iron atoms in the magnetite lattice structure and form titanium hematite after oxidation. Compared with ordinary iron ore, titanium hematite is more difficult to reduce, resulting in a relatively low degree of reduction of vanadium-titanium iron concentrate pellets.

[0005] Patent application CN 117403020A discloses "a method for reducing the low-temperature reduction pulverization rate of vanadium-titanium magnetite gas-based vertical furnace smelting". The method includes maintaining the quality of the reducing gas in the gas-based vertical furnace, including the total content of H2+CO and the ratio of H2 / CO; by using 2-8% CO2 gas to replace N2 in the reducing gas, adjusting the oxidation degree of the reducing gas, and then inhibiting the reduction expansion and pulverization rate of the vanadium-titanium iron concentrate pellets. However, blast furnace smelting is a black box process, and the reducing gas composition in the solid charge area is difficult to regulate. This method is difficult to solve the reduction expansion and pulverization problems of vanadium-titanium iron concentrate pellets in the blast furnace reduction process. Patent CN110484721B discloses "a method for preparing low-reduction pulverized vanadium-titanium magnetite pellets". In order to inhibit the volume expansion of the pellet reduction process, the patent combines the preheating and roasting processes of the vanadium-titanium iron concentrate pellets, roasting them in the range of 950-1150°C for 20-60 minutes to prepare low-reduction pulverized vanadium-titanium iron concentrate pellets. This method successfully solves the problems of reduction expansion and reduction pulverization of vanadium-titanium-iron concentrate pellets, but does not solve the problems of difficulty in reducing vanadium-titanium-iron concentrate pellets and low reduction degree of pellets.

[0006] In addition, when the iron and vanadium resources are recovered by smelting vanadium-titanium iron concentrate using the iron ore agglomeration-blast furnace-converter process, about 40% of the vanadium loss occurs in the blast furnace reduction and converter vanadium blowing process. At present, the overall recovery rate of vanadium in vanadium-titanium magnetite in the Panxi area is less than 50%. The vanadium-titanium iron concentrate calcination-acid leaching vanadium extraction process can significantly improve the recovery rate of vanadium in vanadium-titanium iron concentrate, and has little impact on the subsequent recovery of iron and titanium resources.

[0007] Patent CN.201710217661.3 discloses "a method for calcification oxidation-leaching and vanadium extraction of low-grade chromium-containing vanadium-titanium magnetite". The patent ball-mills the calcified roasted vanadium-titanium iron concentrate into a pellet powder less than 200 mesh, and leaches it in a sulfuric acid system. In the embodiment, the vanadium leaching rate can reach 81.42%. However, the powdery leaching slag after sulfuric acid leaching is difficult to recover economically and efficiently, resulting in a waste of iron and titanium resources. Patent application CN 110317958 A discloses "a method for preparing alkaline oxidation pellets for ironmaking from ferrovanadium materials and extracting vanadium". The method includes the steps of mixing and pelletizing, pellet preparation, vanadium leaching, recovery of vanadium liquid and pellet cleaning, pellet dehydration and drying. After the pellets are dried, they are directly heated to 1100-1300℃ for roasting. After acid leaching, the pellets are dehydrated and dried, and the pellet strength is about 2200N / piece. The compressive strength of the pellets after leaching does not meet the requirements of large blast furnaces for the compressive strength of pellets, and it is not considered whether the other physical and metallurgical properties of the pellets after leaching meet the blast furnace standards.

[0008] In summary, the following problems exist in the blast furnace-converter smelting of alkaline pellets of vanadium-titanium iron concentrate: 1) The vanadium recovery rate in the alkaline pellets of vanadium-titanium iron concentrate is low; 2) The reduction process of the alkaline pellets of vanadium-titanium iron concentrate is severely powdered, and the degree of reduction is relatively low. The process flow of acid leaching of vanadium from alkaline pellets of vanadium-titanium iron concentrate - roasting of residual pellets for vanadium extraction - blast furnace ironmaking still has the following problems: 1) After direct roasting of residual pellets for vanadium extraction, the compressive strength of the roasted pellets is difficult to meet the requirements of the blast furnace; 2) After direct roasting of residual pellets for vanadium extraction, the pellets have low strength, severe powdering, and low degree of reduction. In order to solve the above problems, the present invention proposes a method for preparing high-performance alkaline pellets by acid leaching of vanadium-titanium magnetite concentrate for vanadium extraction. Summary of the invention

[0009] The present invention provides a method of using alkaline pellets of vanadium-titanium iron concentrate as raw materials, extracting vanadium under dilute sulfuric acid leaching and significantly improving the porosity of residual pellets after vanadium extraction; under an optimized roasting thermal system, desulfurization and consolidation of the residual pellets after vanadium extraction are achieved, the compressive strength of the pellets is significantly improved while still maintaining a relatively high porosity of the pellets, and high-performance alkaline pellets are successfully prepared.

[0010] The invention uses vanadium-titanium-iron concentrate as raw material, first prepares vanadium-titanium-iron concentrate alkaline pellets, then leaches the vanadium-titanium-iron concentrate alkaline pellets with dilute acid to obtain vanadium-containing mother liquor, and then roasts the pellets after vanadium extraction with acid to prepare high-performance blast furnace pellets.

[0011] The present invention uses vanadium-titanium-iron concentrate as raw material, first prepares vanadium-titanium-iron concentrate alkaline pellets, uses dilute acid to leach vanadium from the alkaline pellets, soaks the vanadium-extracted residual pellets in a ferrous sulfate solution, and directly roasts the pellets separated from the solid and liquid to obtain alkaline pellets;

[0012] The vanadium-titanium-iron concentrate alkaline pellets contain, by mass percentage, 50-60% TFe, 8-15% TiO2, 0.5-2.0% V2O5; and a binary basicity of 0.6-1.5;

[0013] When dilute acid is used for leaching, the dilute acid solution H + The concentration is 0.1-2 mol / L. After dilute acid leaching, the average compressive strength of the pellets is 500-800N / piece, and the sulfur content is 0.5-1.5%;

[0014] The liquid-to-solid ratio of the ferrous sulfate solution to the vanadium extraction residual balls is 2-10, the mass concentration of the ferrous sulfate solution is 10-50%, and the soaking time is 30-120 minutes;

[0015] The calcination temperature is 1150-1250° C., preferably 1200-1250° C. After calcination, the calcined pellets contain, by mass percentage, 52-62% TFe, 9-16% TiO2, 0.05-0.2% V2O5, and less than 0.005% sulfur.

[0016] The invention discloses a method for preparing high-performance alkaline pellets by acid leaching vanadium from vanadium-titanium magnetite concentrate, wherein the leaching method using dilute acid is selected from heap leaching and column leaching.

[0017] The invention discloses a method for preparing high-performance alkaline pellets by acid leaching vanadium from vanadium-titanium magnetite concentrate, wherein the vanadium leaching rate is greater than or equal to 80%.

[0018] In the present invention, after leaching with dilute sulfuric acid, the sulfur content in the vanadium extraction residual balls increases, the compressive strength of the balls decreases, but the porosity of the balls increases significantly. In order to ensure the strength of subsequent products, the acid concentration and leaching time need to be controlled to ensure that the average compressive strength of the vanadium extraction residual balls is 500-800N / piece and the sulfur content is 0.5-1.5%.

[0019] In the present invention, the pellet strength after acid leaching and vanadium extraction by ferrous sulfate solution soaking treatment meets the requirements and can be directly roasted. The roasting temperature is 1100-1250°C and the roasting time is 10-30 minutes. The roasting process realizes the desulfurization and reconsolidation of the vanadium extraction residual pellets, improves the compressive strength of the pellets, reduces the sulfur content of the pellets, but still maintains a large porosity of the pellets.

[0020] In the present invention, the compressive strength of the calcined product is greater than 2500N / piece.

[0021] In the present invention, the calcination temperature is 1150-1200°C. After calcination, the calcined pellets have, by mass percentage, TFe 52-62%, TiO2 9-16%, V2O5 0.1-0.2%, and sulfur content <0.005%.

[0022] The main mechanisms involved in this patent are as follows:

[0023] Dilute sulfuric acid leaching of vanadium-titanium iron concentrate alkaline pellets can selectively extract vanadium, and the leaching rate of iron is low. During the sulfuric acid leaching process, calcium compounds react with sulfuric acid to selectively dissolve vanadium, while calcium ions react with sulfate ions to form calcium sulfate and remain in the pellets. Therefore, calcium will hardly be lost during the acid leaching process, and will not affect the alkalinity of the roasted pellets. A large number of micropores are formed inside the pellets, resulting in a significant increase in the porosity of the vanadium extraction residual balls and a decrease in the compressive strength of the vanadium extraction residual balls.

[0024] The main sulfur-containing phase in the vanadium extraction residual ball is calcium sulfate, which can be directly roasted to decompose calcium sulfate and achieve desulfurization of the pellets. The TG-DSC curve of the vanadium extraction residual ball is as follows: Figure 1As shown in the figure, the significant decomposition of calcium sulfate mainly occurs in the stage of 1050-1100℃, so the direct roasting temperature should be higher than 1100℃. By controlling the roasting temperature and roasting time (roasting temperature is 1150-1250℃, roasting time is 15-30min), the desulfurization of the pellets can be achieved, and at the same time, the connection between the titanium hematite microcrystalline bonds and the slag phase inside the roasted pellets can be strengthened, which significantly improves the strength of the roasted pellets. During the ferrous sulfate leaching process of the vanadium-extracted residual pellets, ferrous sulfate diffuses into the pores of the pellets. During the roasting of the residual pellets, the iron oxide decomposed by ferrous sulfate undergoes a crystallization effect in the pores of the residual pellets, which plays a role in auxiliary consolidation, and is conducive to improving the strength of the roasted pellets at a lower roasting temperature. The consolidation of the calcined pellets prepared by the present invention is mainly connected by the microcrystalline bonds of titanium hematite and silicate. The silicate does not react during the reduction process, but still serves as a connecting bridge after reduction to tightly connect the titanium-containing fusite, ilmenite and ilmenite crystal, so that the calcined pellets have lower reduction expansion and higher reduction powdering RDI. +3.15mm Therefore, the physical and metallurgical properties of the roasted pellets prepared by roasting the vanadium-extracted residual balls have reached the first-class blast furnace product standards. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the thermogravimetric analysis (TG-DSC) diagram of vanadium extraction residual balls;

[0026] Figure 2 This is a physical picture of the roasted pellets in the embodiment;

[0027] Figure 3 This is a physical picture of the reduction and pulverization of the calcined pellets in the example. DETAILED DESCRIPTION

[0028] The present invention is further described below with reference to specific embodiments. The illustrative embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0029] Typical physical properties of the vanadium-titanium-iron concentrate alkaline pellets used in the examples of the present invention and the comparative examples are shown in Table 1, and typical chemical compositions of the vanadium-titanium-iron concentrate alkaline pellets are shown in Table 2.

[0030] Table 1. Typical physical properties of vanadium-titanium iron concentrate alkaline pellets

[0031] Average compressive strength / (N / piece) Average particle size / mm Porosity / % 1934.7 11.91 21.49

[0032] Table 2. Typical chemical composition of vanadium-titanium iron concentrate alkaline pellets

[0033]

[0034]

[0035] Example 1

[0036] 500g of pellets were placed in a 1000ml measuring cylinder and leached at room temperature. The liquid-to-solid ratio was 2 and the acid concentration of the leaching solution [H + ] is 2.0M, and the acid is added every day according to the consumption of leaching liquid. After 27 days of immersion and 1 day of washing, the vanadium leaching rate is 80.64%. After liquid-solid separation, vanadium extraction residual balls are obtained, and their basic physical properties and chemical composition are shown in Table 1-1 and Table 1-2.

[0037] Table 1-1 Typical physical properties of vanadium-extracted residual balls

[0038] Average compressive strength / (N / piece) Average particle size / mm Porosity / % 508.7 11.78 27.26

[0039] Table 1-2 Typical chemical composition of vanadium-extracting pellets

[0040] Components TFe FeO CaO <![CDATA[Al2O3]]> <![CDATA[SiO2]]> MgO <![CDATA[TiO2]]> Wt% 56.38 0.45 0.90 1.89 1.20 2.05 10.98 Components <![CDATA[V2O5]]> <![CDATA[Cr2O3]]> MnO S <![CDATA[R2]]> Wt% 0.14 0.15 0.18 0.50 0.75

[0041] The above vanadium extraction residual balls were soaked in a 20% ferrous sulfate solution for 60 minutes, with a liquid-to-solid ratio of 5:1. The soaked residual balls were roasted in a rotary kiln at 1100℃, 1150℃, 1200℃, and 1250℃ for 20 minutes. The average compressive strength of the roasted balls was 1515N / piece, 2508N / piece, 2729N / piece, and 3158N / piece, respectively. The sulfur content of the roasted balls was 0.24%, 0.12%, 0.055%, 0.056%, and 0.026%, respectively. The porosity of the roasted balls was 26.97%, 26.70%, 26.62%, and 26.26%, respectively. The results show that the use of a rotary kiln to directly roast vanadium extraction residual balls can prepare roasted balls with low sulfur content, high porosity, and qualified compressive strength. With the increase of roasting temperature, the compressive strength of the roasted balls increased significantly, and the sulfur content and porosity of the balls decreased. The main chemical components of the calcined pellets are shown in Table 2-1.

[0042] Table 2-1 Typical chemical composition of roasted pellets

[0043] Components TFe FeO CaO <![CDATA[Al2O3]]> <![CDATA[SiO2]]> MgO <![CDATA[TiO2]]> Wt% 57.62 0.40 1.01 1.77 1.28 1.86 11.31 Components <![CDATA[V2O5]]> <![CDATA[Cr2O3]]> MnO S <![CDATA[R2]]> Wt% 0.15 0.13 0.14 0.0049 0.79

[0044] Example 3

[0045] The above vanadium extraction residual balls were soaked in a 10% ferrous sulfate solution for 120 minutes, with a liquid-solid ratio of 3:1. The soaked residual balls were roasted in a rotary kiln at 1200℃ for 10 minutes, 20 minutes, and 30 minutes. The average compressive strength of the roasted pellets was 2579N / piece, 2646N / piece, and 2819N / piece, respectively. The sulfur content of the roasted pellets was 0.087%, 0.056%, and 0.0033%, respectively. The porosity of the roasted pellets was 28.17%, 26.44%, and 25.26%, respectively. The results show that as the roasting time increases, the average compressive strength of the roasted pellets gradually increases, and the sulfur content and pellet porosity gradually decrease. However, the roasted pellets still maintain a high porosity.

[0046] Example 4

[0047] The above vanadium extraction residual balls were soaked in a 50% ferrous sulfate solution for 30 minutes, with a liquid-to-solid ratio of 5:1. The soaked residual balls were roasted at 1200°C for 20 minutes using a belt mill. The average compressive strength of the roasted balls was 2565N / piece, and the porosity of the balls was 26.15%. Figure 2 The roasted pellets and the basic pellets of vanadium-titanium iron concentrate without acid leaching were used as raw materials for blast furnace metallurgical performance tests. The metallurgical performance results of different pellets are shown in Table 4-1. Figure 3 As shown. The reduction degree of the alkaline pellets of vanadium-titanium iron concentrate is only 69.89%, while the reduction degree of the roasted pellets can reach 81.13%. At the same time, the roasted pellets have a lower reduction expansion rate and a higher reduction pulverization rate. Therefore, compared with the alkaline pellets of vanadium-titanium iron concentrate, the alkaline pellets prepared by the present invention have better metallurgical properties. Compared with the national standard GB / T 27692-2024, the roasted pellets prepared by the present invention meet the first-class requirements of pellets for blast furnaces.

[0048] Table 4-1 Metallurgical properties of different pellets

[0049] Pellet Type RSI / % RI / % <![CDATA[DRI +3.15mm / %]]> National standard first-class product ≤15.0 ≥80.0 ≥85.0 Vanadium-titanium iron concentrate basic pellets 16.78 69.89 89.42 Roasted pellets 8.07 86.13 96.89

[0050] Comparative Example 1

[0051] The raw material vanadium titanium iron concentrate alkaline pellets are the same as those in Example 1, except that the vanadium titanium iron concentrate alkaline pellets are not subjected to sulfuric acid leaching, but are directly roasted at 1250°C for 20 minutes. The average compressive strength of the pellets is 2216.2N / piece, and the porosity of the roasted pellets is 15.48%. The pellets are used as raw materials to test the blast furnace metallurgical properties. The pellet reduction expansion RSI is 18.27%, the reduction degree RI is 60.48%, and the reduction powder DRI is 1.34%. +3.15mm =83.80%, and its metallurgical properties are obviously lower than those of the calcined pellets prepared by the present invention in Example 4.

[0052] Comparative Example 2

[0053] The raw material vanadium extraction pellets are the same as those in Example 4, except that: the vanadium extraction residual pellets are not soaked in ferrous sulfate, and other systems remain unchanged. The residual pellets are roasted at 1200°C for 20 minutes using a belt mill. The average compressive strength of the roasted pellets is 2125N / piece, the pellet porosity is 28.15%, and the sulfur content of the roasted pellets is 0.0026%. The roasted pellets are used as raw materials to test the blast furnace metallurgical properties. The pellet reduction expansion RSI is 15.35%, the reduction degree RI is 73.25%, and the reduction powder DRI is 0.0026%. +3.15mm =89.35%, and its metallurgical properties are obviously lower than those of the calcined pellets prepared by the present invention in Example 4.

[0054] Comparative Example 3

[0055] The raw material vanadium extraction pellets are consistent with those in Example 2, except that the binary basicity of the vanadium extraction pellets is 0.4. After calcination at 1250°C for 20 minutes, the average compressive strength of the calcined pellets is 2372.8N / piece, the pellet porosity is 25.69%, and the sulfur content of the calcined pellets is 0.052%. The calcined pellets are used as raw materials to carry out blast furnace metallurgical performance tests, and the pellet reduction expansion RSI is 17.06%, the reduction degree RI is 70.19%, and the reduction powder DRI is 0.052%. +3.15mm =88.55%, the reduction expansion and reduction pulverization properties of the pellets are significantly deteriorated, and the metallurgical properties are significantly lower than those of the calcined pellets prepared by the present invention in Example 4.

Claims

1. A method for preparing high-performance alkaline pellets by acid leaching of vanadium-titanium magnetite concentrate, characterized in that: Using vanadium-titanium-iron concentrate as raw material, alkaline pellets of vanadium-titanium-iron concentrate are first prepared, vanadium is leached out of the alkaline pellets with dilute acid, the residual pellets after vanadium extraction are soaked in ferrous sulfate solution, and the residual pellets separated from solid and liquid are directly roasted to obtain roasted pellets.

2. The method for preparing high-performance alkaline pellets by acid leaching of vanadium-titanium magnetite concentrate according to claim 1, characterized in that: The vanadium-titanium iron concentrate alkaline pellets are calculated by mass percentage, TFe 50-60%, TiO2 8-15%, V2O5 0.5-2.0%; binary basicity 0.6-1.5; When dilute acid is used for leaching, the dilute acid solution H + The concentration is 0.1~2mol / L. After dilute acid leaching, the average compressive strength of the pellets is 500~800N / piece; The liquid-to-solid ratio of the ferrous sulfate solution to the vanadium extraction residual balls is 2-10, the mass concentration of the ferrous sulfate solution is 10-50%, and the soaking time is 30-120 minutes; The calcination temperature is 1150-1250° C. After calcination, the calcined pellets have, by mass percentage, TFe 52-62%, TiO2 9-16%, V2O5 0.05-0.2%, and sulfur content <0.005%.

3. The method for preparing high-performance alkaline pellets by acid leaching of vanadium-titanium magnetite concentrate according to claim 1, characterized in that: The leaching method using dilute acid is selected from heap leaching and column leaching.

4. The method for preparing high-performance alkaline pellets by acid leaching of vanadium-titanium magnetite concentrate according to claim 1, characterized in that: The vanadium leaching rate is greater than 80%.

5. The method for preparing high-performance alkaline pellets by acid leaching of vanadium-titanium magnetite concentrate according to claim 1, characterized in that: The residual ball roasting equipment uses a rotary kiln or a belt machine, the roasting temperature is 1100~1250℃, and the roasting time is 10~30min.

6. The method for preparing high-performance alkaline pellets by acid leaching of vanadium-titanium magnetite concentrate according to claim 1, characterized in that: The compressive strength of the roasted pellets is greater than 2500N / piece, and the metallurgical properties of the pellets meet the high-performance alkaline pellet requirements of the first-grade pellets for blast furnaces.

Citation Information

Patent Citations

  • Method for preparing alkaline oxidation pellets for ironmaking from ferrovanadium material and extracting vanadium

    CN110317958A

  • A method for preparing low-reduction pulverized vanadium-titanium magnetite pellets

    CN110484721B

  • Method for reducing low-temperature reduction degradation rate of vanadium titano-magnetite in gas-based shaft furnace smelting

    CN117403020A